The new Belostoma fittkaui species group with supplemental descriptions of B. fittkaui De Carlo and B. sayagoi De Carlo - Stefanello, Fabiano (Zootaxa, 2021)
The giant water bug fauna from tropical South America remains poorly known. Three species of Belostoma Latreille (Belostoma fittkaui De Carlo, B. sayagoi De Carlo and B. hirsutum Roback & Nieser) have been cited only a few times in the literature. These three species are remarkable since they represent an extreme variation for the genus, with article II of the labium distinctly shorter than article III. Here, the synonymy of B. hirsutum with B. sayagoi is proposed based on examination of type material and additional specimens. Further, B. fittkaui and B. sayagoi are redescribed, including discussion about comparative morphology with congeners. A new species group is proposed for these species and a key to the Belostoma species groups is provided. Distribution records are also updated.